Analysis of Community Preparedness for Disaster Hazards in Pangandaran Regency - Taqwa Putra Budi Purnomo Sidi Hiram; Abdul Haris Achadi (Poltanesa, 2026)
Pangandaran Regency, located on the southern coast of Java, is highly exposed to earthquake and tsunami hazards. This vulnerability is intensified by low-lying coastal landforms, dense coastal development, and tourism activities that increase population exposure and complicate evacuation. In this context, disaster preparedness should not be understood solely as the availability of evacuation infrastructure, but as a socially and institutionally constructed capacity. This study examines disaster preparedness in Pangandaran by focusing on collaborative leadership and stakeholder communication in local disaster governance. A qualitative case study design was employed from May to August 2025. Data were collected through semi-structured interviews with three key informants representing formal institutions, volunteer groups, and the local community, supported by limited field observation. The data were analyzed thematically. The findings indicate that preparedness in Pangandaran is shaped by four interrelated dimensions: coordinative, communicative, structural-operational, and social-learning preparedness. Preparedness has been strengthened through cross-actor coordination, information verification, evacuation shelters and routes, and simulation-based learning. However, important limitations remain. Coordination still tends to center on formal actors, risk communication must operate in a dense tourism setting with diverse audiences, evacuation infrastructure is constrained by uneven access, limited visibility, and shelter capacity, and preparedness is not equally distributed across residents, newcomers, and visitors. Conceptually, this study argues that collaborative leadership in local disaster settings is not merely the presence of multiple actors, but a functional yet unequal arrangement shaped by trusted communication, role integration, and the translation of risk knowledge into collective action.